How Judges think about racial disparities: situational decision-making in the crimal justice system - Clair, Matthew (Criminology, 2016)
Researchers have theorized how judges’ decision-making may result in the disproportionate presence of Blacks and Latinos in the criminal justice system. Yet, we have little evidence about how judges make sense of these disparities and what, if anything, they do to address them. By drawing on 59 interviews with state judges in a Northeastern state, we describe, and trace the implications of, judges’ understandings of racial disparities at arraignment, plea hearings, jury selection, and sentencing. Most judges in our sample attribute disparities, in part, to differential treatment by themselves and/or other criminal justice officials, whereas some judges attribute disparities only to the disparate impact of poverty and differences in offending rates. To address disparities, judges report employing two categories of strategies: noninterventionist and interventionist. Noninterventionist strategies concern only a judge's own differential treatment, whereas interventionist strategies concern other actors’ possible differential treatment, as well as the disparate impact of poverty and facially neutral laws. We reveal how the use of noninterventionist strategies by most judges unintentionally reproduces disparities. Through our examination of judges’ understandings of racial disparities throughout the court process, we enhance understandings of American racial inequality and theorize a situational approach to decision-making in organizational contexts.